2007
DOI: 10.1016/j.scitotenv.2007.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Dissolved organic matter fluorescence as a water-flow tracer in the tropical wetland of Pantanal of Nhecolândia, Brazil

Abstract: The Nhecolândia is a sub-region of the Brazilian Pantanal wetland, where saline and freshwater lakes coexist in close proximity. Measurements of dissolved organic carbon (DOC) content and analysis of fluorescence excitation-emission matrices (EEM) were conducted in an effort to characterize spatial variability in concentration and source of dissolved organic matter (DOM) and to further understand the hydrochemical functioning of this complex environment. Increasing pH under the influence of evaporation resulte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
0
10

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 23 publications
5
26
0
10
Order By: Relevance
“…The study highlights an important interaction between the saline and freshwater lakes, which has implications for the functioning of the Pantanal ecosystem, involving dissolution and transfer of chemical elements and organic matter (Mariot et al, 2007). It confirms that the co-existence of saline and freshwater lakes is due to a differential hydrological regime, where the freshwater is directed towards the depressions of the saline lakes.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…The study highlights an important interaction between the saline and freshwater lakes, which has implications for the functioning of the Pantanal ecosystem, involving dissolution and transfer of chemical elements and organic matter (Mariot et al, 2007). It confirms that the co-existence of saline and freshwater lakes is due to a differential hydrological regime, where the freshwater is directed towards the depressions of the saline lakes.…”
Section: Discussionsupporting
confidence: 52%
“…Usual pKa values for natural organic matter are determined by the two most abundant functional groups, 4.7 (carboxyl group) and 10 (phenol group). Consequently, at the observed pH values the dissolved organic compounds are mostly anionic and are also partly contributing to the high electrical conductivity (Mariot et al, 2007). (Goldberg, 2002).…”
Section: Evaporation Concentration and Associated Precipitationsmentioning
confidence: 94%
“…Comparison of DOC-conductivity relationships among saline lakes globally. Regressions from regions other than this study were calculated on data presented in the referenced study (data were estimated averages from Mariot et al 2007 None of these studies consider DOM photodegradation as a contributing factor to CO 2 flux from saline lake surface waters, although our results and those of Waiser and Robarts (2004) clearly demonstrate the importance of photodegradation in saline lake carbon cycles.…”
Section: Discussionmentioning
confidence: 89%
“…According to Rezende Filho et al (2012), the gradual and continuous chemical changes from the most diluted to the most concentrated waters allowed to link their origin to the chemistry of the Taquari River freshwater that supply the region. Nhecolândia has relatively closed drainage with little connection to major 20 fluvial systems, and therefore, the organic matter in the lakes depends more on the local cycles than on terrestrial inputs by the annual inundation pulse (Mariot et al, 2007). Semihumid climate patterns, classified as tropical humid with short dry season ("Aw" type in the Köppen classification), are controlled by the seasonal migration of the Intertropical Convergence Zone (ITCZ).…”
Section: Studied Areamentioning
confidence: 99%
“…Furian et al (2013) have shown that the level of salinity of neighboring lakes are independent and that the co-20 existence of both, saline and freshwater lakes occurs as a result of the distribution of the soil cover that induce a differential hydrological regime. Under the influence of cumulative evaporation over the years, the pH of some saline lakes has reached high values, close to or above 10, resulting in an increasing solubility of the organic matter, with dissolved organic carbon (DOC) values up to 750 mg L -1 (Barbiero et al, 2016;Mariot et al, 2007). Martins (2012) noticed that waters of neighboring saline lakes with almost similar chemical composition can have permanent black or green color, resulting from opposite 25 biogeochemical functioning, but the parameters that control such differences are still poorly understood.…”
Section: Introductionmentioning
confidence: 99%